A Path Towards Green University: A Case Study of Mid-West University - Gaire, Nabin (Journal of Entrepreneurship & Management Studies, 2024)
As sustainability becomes an increasingly crucial global imperative, educational institutions play a vital role in shaping environmentally responsible leaders and fostering sustainable practices. This research article presents a case study titled "A Path Towards Green University: A Case Study of Mid-West University," which explores the transformative journey of Mid-West University towards becoming an eco-friendly and sustainable institution. The study investigates the various initiatives and strategies implemented by the university to reduce its environmental impact, promote sustainable behavior among stakeholders, and achieve its sustainability goals.The research used a qualitative approach to comprehensively understand the university's sustainability efforts. Interviews provided detailed information about the motivations, challenges, and strategies involved in the green transformation. Additionally, quantitative data from surveys and institutional records offered measurable progress indicators, such as reduction in energy consumption, waste diversion percentages, and changes in sustainability-related curriculum offerings.